2011
DOI: 10.1016/j.foodpol.2011.09.001
|View full text |Cite
|
Sign up to set email alerts
|

What is the irrigation potential for Africa? A combined biophysical and socioeconomic approach

Abstract: , the Discussion Paper series within each division and the Director General's Office of IFPRI were merged into one IFPRI-wide Discussion Paper series. The new series begins with number 00689, reflecting the prior publication of 688 discussion papers within the dispersed series. The earlier series are available on IFPRI's website at http://www.ifpri.org/publications/results/taxonomy%3A468. 2 IFPRI Discussion Papers contain preliminary material and research results. They have been peer reviewed, but have not bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
239
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 304 publications
(241 citation statements)
references
References 3 publications
1
239
1
Order By: Relevance
“…The contribution of investments in irrigation adapted to changing socio-economic and environmental conditions is expected to remain critical for future food production across the world (Magistro et al, 2007;Turral et al, 2010;World Bank, 2007;You et al, 2011). You et al (2011 found significant profitable irrigation potential for small-scale and large-scale systems in Africa.…”
Section: Importance Of Investments In Agricultural Water and Irrigatimentioning
confidence: 99%
See 3 more Smart Citations
“…The contribution of investments in irrigation adapted to changing socio-economic and environmental conditions is expected to remain critical for future food production across the world (Magistro et al, 2007;Turral et al, 2010;World Bank, 2007;You et al, 2011). You et al (2011 found significant profitable irrigation potential for small-scale and large-scale systems in Africa.…”
Section: Importance Of Investments In Agricultural Water and Irrigatimentioning
confidence: 99%
“…This means that more efforts are required to ensure investments in irrigation are aligned with developmental priorities/goals/policies of the countries (Turral et al, 2010), including ensuring that changes in water scarcity and quality are integrated in the planning and implementation of irrigation investments. In addition, there is a need for improved knowledge of niche areas that have greatest potential for irrigation, as part of efforts to expand the area under irrigation in Africa (You et al, 2011).…”
Section: Importance Of Investments In Agricultural Water and Irrigatimentioning
confidence: 99%
See 2 more Smart Citations
“…To decrease hunger the outputs in agriculture will need to increase, and thus the water use. The data has been calculated for developing countries with minimum set of calories (Stockholm Environment Institute 2005 ) Furthermore, developed irrigation potential is more than 100 % -Algeria (112 %), Barbados (152 %), Cyprus (109 %), Libya (175 %), and Malta (160 %) and it may apply for other countries in the future based on considerable growth of this index in recent years (FAO 2013 ;You et al 2011 ). Therefore, compared to the decrease in agricultural water withdrawal (Fig.…”
Section: Fig 182mentioning
confidence: 99%